Machines as Analysts: AI-Assisted Decision-Making and Evidence Interpretation in Forensic Science - Pallavi A Rao (AG Volumes, 2026)
Forensic science now utilizes artificial intelligence (AI) as a decision support tool to improve the interpretation, analysis, and evaluation of increasingly complex evidence. This review focuses on pattern recognition, image and multimedia analysis, DNA interpretation, and medical forensics as major forensic applications that employ AI-assisted decision making. It explains the basics of artificial intelligence, machine learning and deep learning, as well as the process for AI support in forensic decision making. The review also takes into account the scientific reliability, explainability of AI, validation of the models, transparency of the algorithm, and the legal admissibility of AI generated evidences in Indian legal landscape in light of the Bharatiya Sakshya Adhiniyam, 2023. Finally, it highlights current challenges, future technological developments, and the importance of human–AI collaboration. The review recommends that AI is a scientifically developed decision support tool that is used alongside forensic analysis to provide accurate, transparent and legally defensible evidence interpretation.